2007
DOI: 10.1073/pnas.0705988104
|View full text |Cite
|
Sign up to set email alerts
|

The role of fluctuations in tRNA selection by the ribosome

Abstract: The detailed mechanism of how the ribosome decodes protein sequence information with an abnormally high accuracy, after 40 years of study, remains elusive. A critical element in selecting correct transfer RNA (tRNA) transferring correct amino acid is ''induced fit'' between the ribosome and tRNA. By using singlemolecule methods, the induced fit mechanism is shown to position favorably the correct tRNA after initial codon recognition. We provide evidence that this difference in positioning and thermal fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
144
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(156 citation statements)
references
References 29 publications
11
144
1
Order By: Relevance
“…Recent work has demonstrated the utility of singlemolecule detection of fluorescent tRNAs in elucidating mechanistic details of tRNA interactions with the ribosome (Blanchard et al 2004a,b;Lee et al 2007;Munro et al 2007;Fei et al 2008). Although Zachau and his coworkers and others had demonstrated that several RNH 2 compounds (e.g., amines, hydrazines, hydrazides) could, in principle, be used to replace dihydroU within tRNA Zachau 1974, 1979;Yang and Söll 1974), as a practical manner, most studies of tRNA-ribosome interaction using this approach have focused virtually exclusively on proflavin-labeled tRNA (Rodnina et al 1994(Rodnina et al , 1997Pape et al 1998;Savelsbergh et al 2003;Pan et al 2006Pan et al , 2007Grigoriadou et al 2007a,b;Kothe and Rodnina 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated the utility of singlemolecule detection of fluorescent tRNAs in elucidating mechanistic details of tRNA interactions with the ribosome (Blanchard et al 2004a,b;Lee et al 2007;Munro et al 2007;Fei et al 2008). Although Zachau and his coworkers and others had demonstrated that several RNH 2 compounds (e.g., amines, hydrazines, hydrazides) could, in principle, be used to replace dihydroU within tRNA Zachau 1974, 1979;Yang and Söll 1974), as a practical manner, most studies of tRNA-ribosome interaction using this approach have focused virtually exclusively on proflavin-labeled tRNA (Rodnina et al 1994(Rodnina et al , 1997Pape et al 1998;Savelsbergh et al 2003;Pan et al 2006Pan et al , 2007Grigoriadou et al 2007a,b;Kothe and Rodnina 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We turned to a combination of single-molecule and ensemble methods to adequately identify the nature and steps anticipated along the PCNA loading-unloading pathways (27,28). Using primarily the FRET signals from a fluorescently labeled forked-DNA and PCNA, we obtained data that indicate (i) PCNA loading on DNA proceeds through a series of conformational intermediates and is successful after multiple failed attempts; (ii) RFC loads PCNA stoichiometrically and does not act catalytically on a primed 45-mer templated fork; (iii) the RFC · PCNA · DNA complex formed in the presence of ATP consists of at least two noninterconverting populations; (iv) the species of the RFC · PCNA · DNA complex disassemble either slowly through disassociation of the PCNA into its component subunits, a process that is independent of RFC and ATP/ATPγS levels, or through a more rapid recycling of intact PCNA; and (v) in the presence of polδ, a population of the RFC · PCNA · DNA complex is converted to the RFC · PCNA · DNA · polδ holoenzyme.…”
mentioning
confidence: 99%
“…3,5 This approach has been applied to monitor folding of biopolymers (proteins and nucleic acids), [7][8][9] enzyme-substrate complex formation, [10][11][12][13][14] and the operation of molecular motors. [15][16][17][18][19][20] A persistent issue in such studies is that they explicitly follow the dynamics of one, or at most a few, of the many degrees of freedom of a macromolecular system. In other words, the measurement is a projection of the full dynamics.…”
Section: Introductionmentioning
confidence: 99%